How traditional preparation methods affect the nutritional composition of Lupin and Soy - Douch, Adam (2023)
Awareness of the health benefits associated with reducing the consumption of animal products has led to an increase in the development of meat alternatives. Many of these alternatives rely on soybean because of its adaptability in producing a palatable meat alternative, such as Tempeh and Tofu. However, many are falling out of favour of soy as its consumption is linked to deforestation and loss of biodiversity. Furthermore, most of soy is imported into the UK therefore carbon footprint has to be taken into consideration. Lupin bean is deemed a possible alternative for soy as they can be cultivated in the UK and have many environmental benefits including nitrogen fixing, but its nutritional composition in comparison to soy is unknown particularly following processing by fermentation to produce tempeh and the coagulating to produce tofu. Thus the aim of this project was to compare the nutritional profile, focussing on protein and amino acid content, of soy and lupin beans. We observed that boiling the raw soy and lupin beans significantly increased the water content but decreased in nutritional content (energy, fats and protein). However while fermentation (process for the production of tempeh) increased the protein content in both beans the amino acid content was different. Fermentation increased the levels of branch chain amino acids (BCAA) in lupin while decreasing them in soy, although further frying of the soy increased it to greater levels of that of lupin where no further increase was observed. It was found that a processing method can influence the nutritional content of these products, however it was found that the Soy tempeh BCAA actually adapted best to the frying.